A balanced ultra‐wideband bandpass filter based on H‐type sandwich slotline. Issue 5 (20th February 2021) - Sun, Jing; Li, Guang Rui
Abstract: In this paper, a balanced ultra‐wideband (UWB) band‐pass filter (BPF) with compact size and simple structure is proposed. The proposed filter is fed by microstrip‐slotline transition structures. A UWB differential‐mode (DM) passband is achieved by employing H‐type sandwich slotline structure. The fractional bandwidth of proposed balanced BPF could reach as much as 132%. In order to improve the selectivity, a source‐load coupling is introduced. Meanwhile, one more layer of substrate is employed to reduce the DM passband insert loss. In addition, due to the symmetrical structure, a high UWB common‐mode suppression without influencing the DM passband is realized. Therefore, the filter design method can be simplified significantly. In order to validate the effectiveness of the design method, a balanced UWB BPF is fabricated and the simulated results agree well with the measured ones.